Alternatives to local content - Ivar Kolstad; Abel Kinyondo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper suggests that an optimal local content policy in the context of flawed institutions is a more minimal one than those typically pursued by developing countries with recently discovered petroleum reserves. We argue that local content requirements need to be seen as a public expenditure question: such requirements increase multinationals' costs and hence reduce the taxes that can be extracted from these companies. There are thus opportunity costs in imposing local content requirements, since the forgone taxes could be used in other ways to improve development prospects. Such requirements can also exacerbate key problems of patronage and rent-seeking.
Keywords: D72; D73; O14; Q32; 330; local content; natural gas; oil; petroleum; Tanzania